USAGE OF SET EXPRESSIONS AND PHRASEOLOGICAL UNITS IN ENGLISH - Mirzayeva Mohiraxon Qoʻldashali qizi; Sotvoldiyeva Muyassar (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This paper is devoted to the analysis of the usage of set expresssions and phraseological units in English. The expressions and phraseological units is of great importance in learning language and vocabulary. They describe thoughts and give people’s utterance which is not impossible to understand by other means. The results and examples of this paper can help to distinguish some important qualities in the meanings of phraseological units and set expressions in learning English.